Research Commentary—Platform Evolution: Coevolution of Platform Architecture, Governance, and Environmental Dynamics - Tiwana, Amrit; Konsynski, Benn; Bush, Ashley A. (Information Systems Research, 2010)
The emergence of software-based platforms is shifting competition toward platform-centric ecosystems, although this phenomenon has not received much attention in information systems research. Our premise is that the coevolution of the design, governance, and environmental dynamics of such ecosystems influences how they evolve. We present a framework for understanding platform-based ecosystems and discuss five broad research questions that present significant research opportunities for contributing homegrown theory about their evolutionary dynamics to the information systems discipline and distinctive information technology-artifact-centric contributions to the strategy, economics, and software engineering reference disciplines.